2022
DOI: 10.1097/wnn.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

BNT–15: Revised Performance Validity Cutoffs and Proposed Clinical Classification Ranges

Abstract: Background: Abbreviated neurocognitive tests offer a practical alternative to full-length versions but often lack clear interpretive guidelines, thereby limiting their clinical utility.Objective: To replicate validity cutoffs for the Boston Naming Test -Short Form (BNT-15) and to introduce a clinical classification system for the BNT-15 as a measure of object-naming skills.Method: We collected data from 43 university students and 46 clinical patients. Classification accuracy was computed against psychometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 121 publications
3
6
0
Order By: Relevance
“…When included in the regression models, sex remained significant in those four countries/regions, showing slightly higher scores in men compared to women. The minimal correlation between sex and 15-item BNT total scores is broadly consistent with other studies examining the BNT standard or short forms that have found no or minimal sex differences (Abeare et al, 2022; Fastenau et al, 1998; Fillenbaum et al, 1997; Mitrushina et al, 2005; Olabarrieta-Landa et al, 2015). Moreover, in the four other countries/regions (i.e., Puerto Rico, Paraguay, Honduras, and El Salvador) showing no differences by sex, there may be specific cultural or gender norms impacting the scores.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When included in the regression models, sex remained significant in those four countries/regions, showing slightly higher scores in men compared to women. The minimal correlation between sex and 15-item BNT total scores is broadly consistent with other studies examining the BNT standard or short forms that have found no or minimal sex differences (Abeare et al, 2022; Fastenau et al, 1998; Fillenbaum et al, 1997; Mitrushina et al, 2005; Olabarrieta-Landa et al, 2015). Moreover, in the four other countries/regions (i.e., Puerto Rico, Paraguay, Honduras, and El Salvador) showing no differences by sex, there may be specific cultural or gender norms impacting the scores.…”
Section: Discussionsupporting
confidence: 87%
“…All countries/regions in this study showed a positive significant correlation (low to moderate in strength) between education and the 15-item BNT total scores. The models showed that 15-item BNT total scores increased with greater years of education across all countries/regions, thus, adding to previous research obtaining similar effects (Abeare et al, 2022;Fernández-Blázquez et al, 2012;Fillenbaum et al, 1997;Olabarrieta-Landa et al, 2015). Interestingly, education was the only factor that was significant across all This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionsupporting
confidence: 75%
“… Specifically computed to convert traditional scores into a binomial experiment; 1–3, Acquisition trials; Animals, Category fluency (Curtis et al., 2008; Hurtubise et al., 2020; Sugarman & Axelrod, 2015); BC, Below chance level (below the 95% confidence interval around the mean); BIN, Cutoff based on the binomial distribution; BNT‐15, Boston Naming Test—Short Form (Abeare et al., 2022; Deloria et al., 2021; Erdodi, Dunn, et al., 2018); C, At chance level (within the 95% confidence interval around the mean); CD WAIS‐IV , Coding (Ashendorf et al., 2017; Erdodi, Abeare, et al., 2017); CIM, Complex Ideational Material (Erdodi, 2019; Erdodi et al., 2016; Erdodi & Roth, 2017); COL, Color Naming; CPT‐3, Conners' Continuous Performance Test—Third Edition ( T = 90 is the highest score possible; Ord et al., 2020; Robinson et al., 2022); COM, Combination score (FR + true positives—false positives); DCT, Dot Counting Test (Boone et al., 2002; Hansen et al., 2022); Dem ADJ , Demographically adjusted score; DH, Dominant hand; D‐KEFS, Delis Kaplan Executive System (Cutler et al., 2022; Eglit et al., 2020; Erdodi, Sagar, et al., 2018); DR, Delayed recall; DS WAIS‐IV , Digit Span subtest of the Wechsler Adult Intelligence Scale—Fourth Edition (Shura et al., 2020; Whitney et al., 2009); EMP, Empirically derived cutoffs; EWFT, Emotion Word Fluency Test (Abeare, Hurtubise, et al., 2021); FAS, Letter fluency (Curtis et al., 2008; Deloria et al., 2021; Hurtubise et al., 2020); FCR, Forced choice recognition; FR, Free recall; FTT, Finger Tapping Test (Arnold et al., 2005; Axelrod et al., 2014; Erdodi, Taylor, et al., 2019); GPB, Grooved Pegboard Test (Erdodi, Kirsch, et al., 2018; Erdodi, Seke, et al., 2017; Link et al., 2021); HVLT‐R, Hopkins Verbal Learning Test—Revised (Cutler et al., 2021; Sawyer et al., 2017); IOP‐M, Inventory of Problems—29 memory module (Giromini et al., 2020a, 2020b; Holcomb, Pyne, et al., 2022); IR, DR & CNS, Immediate, Delayed & Consistency of Recognition trials (% correct); LM Recognition, Yes/No recognition trial of the Logical Memory subtest of the Wechsler Memory Scale—Fourth Edition (Bortnik et al., 2010; Dunn et al., 2021); LNS WAIS‐IV , Letter‐Number Sequencing (Erdodi &amp...…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Sample consisted of 52 adults evaluated to determine their eligibility for disability benefits. The sample was used in previous publications focused on different topics (Abeare, An, et al, 2022; Abeare, Razvi, et al, 2021; Abeare, Romero, et al, 2021; Cutler, Abeare, et al, 2022; Hurtubise, Baher, et al, 2020). Exclusion criteria for all three samples were intellectual disability or dementia.…”
Section: Methodsmentioning
confidence: 99%